Practical nurse students’ misconceptions about infection prevention and control - Eronen Riikka; Helle Laura; Palonen Tuire; Boshuizen Henny P. A. (Springer Link, 2026)
When teaching infection prevention and control (IPC), nursing education tends to focus on skills and fostering good practice rather than challenging students’ thinking. Therefore, students’ misconceptions about IPC receive less attention than they deserve. The purpose of the study was to make an inventory of student nurses’ misconceptions about IPC before instruction and to make these misconceptions visible to teachers. The study was conducted in one vocational institute in Finland and is based on the answers of 29 practical nurse students before IPC training. The students took an online test requiring them to justify their answers to two multiple-true–false questions: 1) What is the main route of transmission between patients in healthcare facilities, and 2) What is the most effective and easiest manner to prevent the spreading of pathogens, e.g., multi-resistant bacteria in long-term care facilities? Analysis of the students’ written justifications resulted in three mental models: 1) the Household Hygiene Model manifesting lay knowledge learned in domestic situations, 2) the Mixed Model consisting of lay knowledge, enriched with some professional knowledge of IPC, and 3) the Transmission Model manifesting a professional understanding of IPC. The first two mental models were considered to be misconceptions. Only one of the participants showed a professional understanding (i.e., the Transmission Model). To conclude, student nurses manifested systematic patterns of misconceptions before instruction. Unless the students are confronted with their misconceptions of IPC during instruction, it is likely that these misconceptions will impede their learning or make learning outcomes transient.